Trends in Tongue Cancer in Tertiary Hospital in West Java for 5 Years: A Retrospective Study - Sari E.S., Rupita; Monty Priosdewo Soemitro (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Oral cavity malignancy is the most common carcinoma of the head and neck. In the Western world, the tongue and floor of the mouth are the most common sites of origin for primary squamous cell carcinoma in the oral cavity. However, data and reports about tongue cancer is still limited, especially in Indonesia. The aim of this study is to get the epidemiological profile of tongue cancer in tertiary hospital in West Java from 2017 – 2021. Methods: This study was a retrospective review of all patients with tongue cancer. The study used data from hospital information system from 2017 to 2021. Data collected were gender, age, histology, lymph node metastases. All data were analyze using statistical analysis program. Results: Of the 120 cases analyzed. Sixty-eight of the 120 cases (56.67%) were found on female. The age group with the most cases was found in group of 51-60 years (35%). Histological examination showed 59 cases (49.17%) were squamous cell carcinoma well-differentiated, 28 cases (23.33%) showed lymph node regional metastases, and one case showed distant metastases to lung. Conclusion: Tongue cancer profile in tertiary hospital in West Java mostly found in female with squamous cell carcinoma well-differentiated showed the most common. Of all cases, the spread to regional lymph nodes is only a few, not reaching thirty percent.